Comparison of early surgical outcomes following anoplasty and limited PSARP for perineal fistula - Bruno Martinez-Leo; Vicente Herrera-Del Prado; Victor Portugal-Moreno; Arturo Godoy-Esquivel; Adriana Castillo-Aguirre; Luis Velasco-Soria; Luis Garcia-Cabello; Miguel Vargas-Gomez (EL-Med-Pub, 2020)
Background: To present the early surgical outcomes of two different surgical methods for the treatment of perineal fistula in patients with anorectal malformation. Material and Methods: Retrospective chart analysis of patients treated with any of the two surgical approaches for perineal fistula treatment during the newborn period, without a colostomy at Academic and Community Pediatric Surgery Reference Hospital during October 1st, 2015 to December 31st, 2018. Results: Twenty-six out of 57 patients of our database met inclusion criteria during the study period. 15 in the anoplasty group and 11 in the Minimal Posterior Sagittal Anorectoplasty (MPSARP); the anoplasty group had more rate of anoplasty dehiscence (4 partial, 6 total - requiring additional stitches, p = 0.027), versus zero in the MPSARP group, albeit there was 1 superficial perineal dehiscence. All surgeries were performed without a previous colostomy. There were no other surgical complications reported, and there was no difference in age, weight, sacral ratio, and associated malformations. Conclusion: Minimal PSARP can be safely done in the newborn patient with a patent perineal fistula.